Blepharoconjunctivitis With Corneal Ulcer in A Pediatric Patient: Case Report - Nanda Sinya Dwi Putri; Hermadi Faried (INSOLOGI: Jurnal Sains dan Teknologi, 2025)
Blepharoconjunctivitis with corneal ulceration in infants is a rare but significant medical condition. This infection is primarily caused by the bacterium Neisseria gonorrhoeae, a Gram-negative diplococcus that does not form spores. Transmission often occurs from mother to infant through a contaminated birth canal. Neisseria gonorrhoeae adheres to conjunctival and corneal epithelial cells via adhesion proteins, triggering an intense inflammatory response and the release of proteolytic enzymes by immune cells like neutrophils. This process leads to progressive corneal damage. If left untreated, the condition can result in corneal ulceration, perforation, and even blindness. Early detection and effective treatment are crucial to prevent serious complications. The global prevalence of urogenital gonorrhea in 2016 was 0.9% in women and 0.7% in men, with a total of 30.6 million cases worldwide. The WHO reported 82.4 million new infections in adults aged 15-49 years in 2020. In infants, the prevalence was 6 per 100,000 in Canada (2000-2011) and approximately 0.4 cases per 100,000 live births per year in the United States (2013-2017). Symptoms in infected patients include eyelid swelling, conjunctival redness, mucopurulent discharge, and eye tenderness. The primary therapy for gonorrheal infection is ceftriaxone, given intravenously or intramuscularly. Prevention involves routine screening and treatment of STIs in pregnant women and the use of prophylactic eye drops for newborns. This case report details the management of gonococcal eye infection that caused corneal ulceration in a pediatric patient.